Association between added sugars and frailty in U.S. adults: a cross-sectional study from the National Health and Nutrition Examination Survey 2007–2018 - Ji, Jian; Qiu, Jie; Tao, Yijing; Xu, Ming; Pei, Bin; Wu, Chaoshen; Huang, Guoxin; Qian, Da (Frontiers in Public Health, 2024)
Objective: There are various detrimental effects of excessive added sugars consumption on health, but the association of added sugars with frailty remains elusive. We aim to examine the association between added sugars intake and frailty among American adults in the present cross-sectional study. Methods: This study is a cross-sectional study based on the NHANES database. Data from NHANES spanning from 2007 to 2018 on frailty, added sugars, and covariates were collected. Added sugars were categorized into quartiles and according to the recommended percentages by institutions. Weighted multivariable logistic regression was employed to analyze the relationship between frailty and added sugars. Subgroup analysis was conducted based on sex, age, BMI, smoking, alcohol consumption, hypertension, and diabetes status. Results: This study included a total of 16,381 participants, with 13,352 (81.51%) in the non-frailty group and 3,029 (18.49%) in the frailty group. We found that added sugars positively associated with frailty, and subgroup analysis showed participants in males, age >60, low BMI, former smoking and alcohol intake, no hypertension, DM were more likely to frailty. Added sugars intake were positively associated with frailty. Subgroup analysis showed that the association was strongest in males, those aged >60y, those with low BMI, former smokers, former alcohol consumers, and in individuals with no hypertension or with DM. When added sugars are classified by energy percentage, the populations in the >25 percentage of energy from added sugars had similar results, more tend to have a higher prevalence of frailty. Conclusion: Added sugars are positively associated with a higher risk of frailty, and the association is stable among different populations.